THREAT OF BANKRUPTCY DUE TO TERMINATION OF EMPLOYMENT DUE TO THE COVID-19 PANDEMIC - Iskandar Muda Sipayung (International Asia Of Law and Money Laundering, 2022)
One of the consequences of the covid 19 pandemic is that many companies are forced to lay off their employees and make job cuts. The problem is whether the company is allowed to terminate the employment relationship on the grounds of Covid-19 and whether the company can be bankrupt because it is unable to carry out its obligations to its workers. The research method used is lying research using secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. Research is normative juridical and the type of research is qualitative. Conclusion, the company can terminate the employment relationship during Covid-19 on the grounds of Overmacht, if the company can prove that due to the covid-19 pandemic it is no longer able to carry out its obligations towards workers/ laborers. Companies that are unable to fulfill their obligations to their workers can be declared bankrupt and the assets of the seized company are subsequently sold, auctioned for the payment of the rights of the workers who are prioritized for payment. Meaning is to identify and conceptualize the law as a real and functional social institution in a patterned living system